Isolation of Plant Photosystem II Complexes by Fractional Solubilization - Haniewicz, Patrycja; Floris, Davide; Farci, Domenica; Kirkpatrick, Joanna; Loi, Maria C.; Büchel, Claudia; Bochtler, Matthias; Piano, Dario (Frontiers in Plant Science, 2015)
PSII occurs in different forms and supercomplexes in thylakoid membranes. Using a transplastomic strain of Nicotiana tabacum histidine tagged on the subunit PsbE, we have previously shown that a mild extraction protocol with β-dodecylmaltoside enriches PSII characteristic of lamellae and grana margins. Here, we characterize residual granal PSII that is not extracted by this first solubilization step. Using affinity purification, we demonstrate that this PSII fraction consists of PSII-LHCII mega- and supercomplexes, PSII dimers and PSII monomers, which were separated by gel filtration and functionally characterized. Our findings represent an alternative demonstration of different PSII populations in thylakoid membranes, and they make it possible to prepare PSII-LHCII supercomplexes in high yield.